The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3400/avd.oa.14-00071
|View full text |Cite
|
Sign up to set email alerts
|

Management Strategy of Isolated Spontaneous Dissection of the Superior Mesenteric Artery

Abstract: Objective: Isolated spontaneous dissection of the superior mesenteric artery (SMA) is very rare among of the visceral artery dissection and its treatment is not established. In this paper we present our experiences and consider the treatment of isolated SMA dissection. Methods: A retrospective review of our cases from 2005 was performed. Clinical symptoms, radiologic findings and results were evaluated. There were 14 cases of visceral artery dissection, in which all cases were with SMA dissection. There were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 19 publications
1
59
0
Order By: Relevance
“…Majority of patients with SMAD are males in their 50s, 6) and the disease often manifests as sudden abdominal pain. 5) In most patients, administration of conservative treatment results in symptom improvement; however, owing to the dissection of the superior mesenteric artery, in severe cases, there is a risk of intestinal ischemia and ruptures due to dissection. 2,7,8) In patients who visited our department, endovascular treatment was performed because of severe abdominal symptoms associated with acute disease and the possibility of intestinal ischemia in one patient, and surgical blood flow reconstruction was performed in one patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Majority of patients with SMAD are males in their 50s, 6) and the disease often manifests as sudden abdominal pain. 5) In most patients, administration of conservative treatment results in symptom improvement; however, owing to the dissection of the superior mesenteric artery, in severe cases, there is a risk of intestinal ischemia and ruptures due to dissection. 2,7,8) In patients who visited our department, endovascular treatment was performed because of severe abdominal symptoms associated with acute disease and the possibility of intestinal ischemia in one patient, and surgical blood flow reconstruction was performed in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…1). [3][4][5] The following items were evaluated: (1) the pathophysiology of and treatments for acute disease as well as treatment outcomes; (2) evaluation of the dissection morphology of isolated disease using contrast-enhanced computed tomography (CT) as well as the changes caused by dissection; and (3) retrospective chart review of long-term outcomes of isolated disease as well as the collection and review of data from other institutions. ©2019 The Editorial Committee of Annals of Vascular Diseases.…”
Section: Patient Population and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because intestinal ischemia and necrosis are associated with a high mortality rate, delay in the diagnosis of intestinal ischemia or necrosis should be avoided as much as possible [4,5]. There are several choices for assessment of the intestinal condition in such patients such as invasive exploratory laparotomy for laparoscopic vision and exploratory surgery for direct vision [6,7]. On the other hand, it has been reported that the use of computed tomography (CT) with or without contrast medium enhancement has the potential to evaluate the presence or absence of intestinal ischemia and necrosis less invasively than exploratory surgery [8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…[6][7][8][9] Although there were some reports on the role of multi-detector CT in the diagnosis of ISSMAD, the number of cases was limited, and few was more than 20. The case number of the present study was relatively large, and there were 30 cases included.…”
Section: Discussionmentioning
confidence: 99%